2005
DOI: 10.1074/jbc.m412316200
|View full text |Cite
|
Sign up to set email alerts
|

Egg Case Protein-1

Abstract: Spiders produce multiple types of silk that exhibit diverse mechanical properties and biological functions. Most molecular studies of spider silk have focused on fibroins from dragline silk and capture silk, two important silk types involved in the survival of the spider. In our studies we have focused on the characterization of egg case silk, a third silk fiber produced by the black widow spider, Latrodectus hesperus. Analysis of the physical structure of egg case silk using scanning electron microscopy demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Previous studies have demonstrated that two of the abundant proteins represent egg case protein gene products (Fig. 1, lane 2) (14,16). The ϳ300-kDa protein does not represent the major constituent of the large diameter fiber, TuSp1, which is not readily dissolved under these conditions and is missing from detection (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous studies have demonstrated that two of the abundant proteins represent egg case protein gene products (Fig. 1, lane 2) (14,16). The ϳ300-kDa protein does not represent the major constituent of the large diameter fiber, TuSp1, which is not readily dissolved under these conditions and is missing from detection (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Egg sacs must be designed to resist damage from predator/parasitoid invasion as well as temperature and humidity fluctuations (11)(12)(13). Analyses of the physical structure of egg sacs collected from the cob weaver Latrodectus hesperus, commonly referred to as the black widow spider, have demonstrated that their egg case sacs consist of two different diameter fibers (14,15). MS/MS 4 analyses of black widow peptides generated from solubilized egg case materials digested with trypsin have shown that the large diameter core fibers contain the fibroin TuSp1, as well as the egg case proteins ECP-1 and ECP-2 (egg case protein 1 or 2), which form a trimeric complex in cob weavers (14,16,17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of ADF-2, in comparison with additional spidroins, subsequently identified it as a member of the major ampullate spidroin 1 (MaSp1) silk ortholog group (7), used in dragline fibers (13,14). Recently, Hu et al (15) reported another putative component of egg case silk (ECP-1) expressed in silk glands of the black widow spider, Latrodectus hesperus. However, the translated sequence of neither ADF-2 nor ECP-1 could account for the amino acid composition of tubuliform silk fibers or the gland's contents (4,11,15,16,17), indicating that the dominant silk expressed by tubuliform glands must be a different, unidentified protein (4).…”
mentioning
confidence: 99%